Pedagogical aspects of educational television - Asenova, Asya; Dulev, Pavlin (Yearbook Telecommunications, 2018)
Television is a big part of students’ everyday life and thus familiar and enjoyable to them. Therefore, bringing television into the classroom may enhance students’ excitement about the general curriculum. When information is presented in a way that children can relate to, they enjoy learning what is being taught. Although TV is an older technology, teachers can still use it as a great resource for their classes. The purpose of this article is to present and analyze the main features of educational television, types of educational television and programs, steps to implement a programming concept in the field of scientific education.